2020
DOI: 10.2196/17175
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Influential Factors in the Discussion Dynamics of Emerging Health Issues on Social Media: Computational Study

Abstract: Background Social media has become a major resource for observing and understanding public opinions using infodemiology and infoveillance methods, especially during emergencies such as disease outbreaks. For public health agencies, understanding the driving forces of web-based discussions will help deliver more effective and efficient information to general users on social media and the web. Objective The study aimed to identify the major contributors t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…Our initial assessment showed that >75% of tweets and >80% of Weibo posts regarding COVID-19 did not receive any attention on social media. This number is similar to our previous finding that 76% of all Zika-related tweets were never retweeted [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our initial assessment showed that >75% of tweets and >80% of Weibo posts regarding COVID-19 did not receive any attention on social media. This number is similar to our previous finding that 76% of all Zika-related tweets were never retweeted [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, for a large and ongoing pandemic, time is another major influential factor that is associated with the actual progress of the pandemic. Our previous studies showed that the Zika case series was strongly associated with the Zika discussion trend on Twitter in 2016 [ 24 , 25 ]. Similarly, future studies can be expended to explicitly characterize how various content features evolve with time in different regions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations